Available phosphorus in soil from three sources and their effect on biomass and corn root development - Ramírez, Ricardo; SequeraϯOmaira (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
Phosphorus deficiency in the country is very common, to overcome the problem high soluble phosphates are applied, the use a less soluble acidulated phosphate rock with sulfuric acid (RFA) is one economical alternative. The partial substitution of sulfuric acid by ammonium thiosulfate in the acidulation process (R30T) has proven feasible. The objective of this study was to prove the effect of these P sources on the maize behavior. Two soils were used a neutral and acidic one. Four doses of P treatments were used: 0, 70, 140 and 210 mg.kg-1, in a glasshouse experiment. 35 days after planting plants were harvest and soil and root samples were taken for phosphorus analysis and determination of dry matter, root length (LR) and root volume (VR). Partial substitution of sulfuric acid by ammonium thiosulfate does not affect the quality of the acidulated rock. A close relationship between biomass and P concentration in the corn tops with residual soil P, LR and VR increased with the first increase of soil P, successive increments of P produced a decrease in roots size. The LR and VR relationship with P uptake and biomass was not the same in the two soils, in the acidic soil there was a higher dependence on P uptake than in the neutral soil.